Investigation of Operating Operations of Chemical Treaters for Vineyards and Orchards (Texas Journal of Multidisciplinary Studies, 2022)
This article describes the structure, parameters, operating modes, design schemes, areas of application, its operating modes at different speeds, and recommendations for the chemical spraying of vineyards and orchards.